Sensor histidine kinases kdpD and aauS regulate biofilm and virulence in Pseudomonas aeruginosa PA14 - Sultan, Maria; Arya, Rekha; Chaurasia, Akhilesh Kumar; Kim, Kyeong Kyu (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa is a multidrug-resistant opportunistic human pathogen that utilizes two-component systems (TCSs) to sense pathophysiological signals and coordinate virulence.P. aeruginosa contains 64 sensor histidine kinases (HKs) and 72 response regulators (RRs) that play important roles in metabolism, bacterial physiology, and virulence. However, the role of some TCSs in virulence remains uncharacterized. In this study, we evaluated the virulence potential of some uncharacterized sensor HK and RR knockouts in P. aeruginosa using a Galleria mellonella infection model. Furthermore, we demonstrated that KdpD and AauS HKs regulate virulence by affecting P. aeruginosa biofilm formation and motility. Both ΔkdpD and ΔaauS showed reduced biofilm and motility which were confirmed by restored phenotypes upon complementation. Moreover, ΔkdpD and ΔaauS exhibited increased survival of HeLa cells and G. mellonella during in vivo infection. Altered expression of the transcriptional regulators anR and lasR, along with the virulence genes lasA, pelA, cupA, pqsA, pqsB, pqsC, and pqsD in the mutant strains elucidated the mechanism by which ΔkdpD and ΔaauS affect virulence. These findings confirm that kdpD and aauS play important roles in P. aeruginosa pathogenesis by regulating biofilm formation and motility.